2006
DOI: 10.1063/1.2169559
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field sensors based on iron garnets with in-plane magnetization

Abstract: A magnetic-field sensor is proposed that uses thin garnet films with in-plane magnetization and strong magneto-optical activity. The advantages of this sensor are its high intrinsic sensitivity and the possibility of tailoring the field range for linear response. Measurements at 80 Hz yield noise-equivalent magnetic fields of 1.5μT∕Hz and a signal-to-noise ratio of 68 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The root mean square (rms) value of the surface roughness is 1.4 nm which is in agreement with the literature values ranging from 0.2 to 7 nm [10]. Previous studies have showed that the coercive eld is a good indicator of the quality of PLD made YIG lms as a planar waveguide [4,5]. The coercive eld was found to be 5.5 Oe which is small enough for prepared YIG lm to use as a waveguide.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…The root mean square (rms) value of the surface roughness is 1.4 nm which is in agreement with the literature values ranging from 0.2 to 7 nm [10]. Previous studies have showed that the coercive eld is a good indicator of the quality of PLD made YIG lms as a planar waveguide [4,5]. The coercive eld was found to be 5.5 Oe which is small enough for prepared YIG lm to use as a waveguide.…”
Section: Methodssupporting
confidence: 77%
“…In addition, low damping in YIG lms allows spin-wave propagation to be observed over centimeter distances [3]. corresponding author; e-mail: selcuk.atalay@inonu.edu.tr Recently, it has been recognized that YIG lms could be designed as a highly sensitive magnetic eld sensor [4,5]. Conventional magnetic eld sensors have been in use for well hundreds of years.…”
Section: Introductionmentioning
confidence: 99%
“…These films are used in an out-of-plane magnetization configuration as, for example, in [7] or in an in-plane magnetization [4].…”
Section: ) Fiber Optic Coilmentioning
confidence: 99%
“…Several concepts for such sensors based on fiber optic coils [2], bulk rare-earth iron garnets (RIGs) [3], and RIG films [4] have been presented in the past. This paper presents a high-precise optical current sensor based on the Faraday effect ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, magnetic sensors employing spin-wave interferometry in ferrimagnetic films [34,35] or ferrimagnetic resonance (FMR) in spheres [36][37][38] or films [39][40][41][42] have been investigated, including demonstrations with pT/ √ Hz-level sensitivity. Using ferrimagnetic materials, classical sensors such as fluxgates [43][44][45] and Faradayrotation-based devices [46,47] have achieved sensitivities down to 40 fT/ √ Hz and 10 pT/ √ Hz, respectively. Additionally, ferrimagnetic materials have long found commercial use in tunable microwave filters [48,49] and oscillators [50][51][52].…”
Section: Introductionmentioning
confidence: 99%